ADVANCING PRECISION MANUFACTURING: A SCHOLARLY EXPLORATION OF CNC TOOLS - Khujaev Fayzullakhuja (Journals Park Publishing, 2024)
In the realm of contemporary manufacturing, CNC (Computer Numerical Control) tools stand as exemplars of precision engineering and automated efficiency. These tools, governed by intricate computer algorithms, have revolutionized industrial practices across diverse sectors by enabling the meticulous production of complex components with unparalleled accuracy and consistency. This scholarly exploration delves into the multifaceted landscape of CNC tools, elucidating their evolution, typologies, operational mechanics, and transformative impact on modern manufacturing methodologies.
Keywords: CNC (Computer Numerical Control), Precision engineering, Automated efficiency, Manufacturing methodologies, End mills, Drills and taps, Inserts, Reamers and milling cutters, Turning tools, Material compatibility.